Effect of "Tumat" Agro-Mineral Fertilizer on the Productivity of "Andijan-37" Cotton Variety - Tursunov Khayrullo Odiljonovich; Alijonova Gulbakhor Alijon qizi (International Journal on Orange Technologies, 2021)
According to the results of the study, Tumat was treated with argonomireral fertilizer before planting and the concentration was 6.1 grains fed to the cotton during the period of growth and development. Due to the fact that these indicators are 2.6-2.8 more than in our control variant, the seeds of Andijan-37 cotton variety were processed before sowing, and during the growing season, ie during the mowing and flowering period, 40.4 ts / ha of leaf-fed crop was obtained.